Sosialisasi Bahaya Penggunaan Zat Aditif pada Makanan Kemasan di Desa Mendalo Indah Kecamatan Jambi Luar Kota - Teguh Setyawan; Revi Maylina Tanjung; Nur Jaya; Rani Khoiriyah; Melvi Muharmi; Widya Twiny Rizki; Defia Indah Permatasari; Muh. Rizal B; Vebria Ardina; Riskal Fadli; Susanti Aprilina; Pratama, Tio Aditia (Jurnal Pengabdian Masyarakat Pinang Masak, 2026)
Community awareness regarding the safe use of food additives in packaged foods remains relatively low, particularly in understanding the differences between safe and harmful additives and the importance of reading nutritional labels. This condition was also identified among residents of RT 11/RW 03 Valencia Housing Complex, Mendalo Indah Village, Jambi Luar Kota District, where the consumption of packaged and instant foods was relatively high, especially among housewives and children. Therefore, this community service activity aimed to improve public understanding of the hazards of excessive use of synthetic food additives and increase awareness regarding safe food selection. The program was conducted using an educational and participatory approach involving 20 housewives aged 30–60 years. The implementation stages consisted of preparation, educational activities, assistance, and evaluation. Educational materials were delivered through interactive presentations, brochures, discussions, and direct practice in identifying food additives through packaged food labels. The effectiveness of the program was evaluated using pretest and posttest questionnaires. The results showed a significant improvement in participants’ understanding after the educational activities. Participants demonstrated better knowledge regarding the functions of food additives, the hazards of borax use, the identification of potentially harmful additives, and the importance of reading product composition labels. The activity also increased participants’ awareness of selecting safer food products and encouraged healthier consumption behavior within the community.